A Balanced Literacy Initiative for One Suburban School District in the United States. (7th August 2012) - Shaw, Donita; Hurst, Karen
Abstract : The purpose of this study was to investigate how the teachers employed by this suburban USA school district implemented balanced literacy instruction. The 111 teachers who taught grades K-6 completed surveys and were observed. Quantitative data from the surveys and observations were analyzed through descriptive statistics, nonparametric chi-square tests, and Pearson correlations. One open-ended survey question was analyzed qualitatively. Findings show that the majority of teachers had an acceptable understanding of balanced literacy. There were differences among teachers' instruction on literacy components and structures across grades. Weak correlations among self-reported and observed practices were found. Implications are discussed as the data are being used for research-informed improvements in the district.